Airway remodeling and inflammation in competitive swimmers training in indoor chlorinated swimming pools - Bougault, V.; Loubaki, L.; Joubert, P.; Turmel, J.; Couture, C.; Laviolette, M.; Chakir, J.; Boulet, L. P. (Journal of Allergy and Clinical Immunology, 2011)
Airway disorders are common in regular chlorinated swimming pool attendees, particularly competitive athletes, but the impact of intense swimming training on airway function and structure remains unclear.